2022
DOI: 10.3390/plants11131634
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response of Spring Maize under Future Climate and the Effects of Adaptation Measures in Northeast China

Abstract: Agriculture production has been found to be the most sensitive sector to climate change. Northeast China (NEC) is one of the world’s major regions for spring maize production and it has been affected by climate change due to increases in temperature and decreases in sunshine hours and precipitation levels over the past few decades. In this study, the CERES-Maize model-v4.7 was adopted to assess the impact of future climatic change on the yield of spring maize in NEC and the effect of adaptation measures in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Xiao et al. (2020) simulated the future climate by 33 global climate models and two Representative Concentration Pathways, the results of which showed that the annual mean daily radiation decreased in the NCP, and the similar results also were found in the Northeast China (Koimbori, Wang, et al., 2022). Therefore, it is important to increase the light interception of the canopy to reduce the negative effects of the decline in the coming of radiation on maize production.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Xiao et al. (2020) simulated the future climate by 33 global climate models and two Representative Concentration Pathways, the results of which showed that the annual mean daily radiation decreased in the NCP, and the similar results also were found in the Northeast China (Koimbori, Wang, et al., 2022). Therefore, it is important to increase the light interception of the canopy to reduce the negative effects of the decline in the coming of radiation on maize production.…”
Section: Introductionmentioning
confidence: 76%
“…The radiation use efficiency during the vegetative period of maize was usually higher than that during the reproductive period (Shi et al, 2022), but increasing the light interception during the postsilking period can significantly increase the yield of maize (Zhou et al, 2021). Xiao et al (2020) simulated the future climate by 33 global climate models and two Representative Concentration Pathways, the results of which showed that the annual mean daily radiation decreased in the NCP, and the similar results also were found in the Northeast China (Koimbori, Wang, et al, 2022). Therefore, it is important to increase the light interception of the canopy to reduce the negative effects of the decline in the coming of radiation on maize production.…”
Section: Introductionmentioning
confidence: 79%
“…Process-based crop models serve as primary scientific tools for estimating crop yield, assessing the impact of environmental changes, and guiding adaptive measures under climate change [4,7,8]. Crop productivity is intricately linked to crop phenology [9,10], which is significantly influenced by climate, including changes due to warming trends [11][12][13][14][15]. In the phenological stages of crops, the timing of planting significantly impacts crop productivity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Given the scarcity of water resources in Heilongjiang Province and the crucial role of precipitation in agricultural water supply, research into the spatial distribution irregularities of precipitation in the province holds significant practical significance. Such studies can further our understanding of both flood and drought events [33] and help assess the tangible impact of precipitation disparities on the growth of rainfed crops [34][35][36]. Research data used in this study comprise daily precipitation records from 29 meteorological observation stations in Heilongjiang Province spanning from 1961 to 2020.…”
Section: Introductionmentioning
confidence: 99%